2006
DOI: 10.1002/humu.20363
|View full text |Cite
|
Sign up to set email alerts
|

An automated procedure to identify biomedical articles that contain cancer-associated gene variants

Abstract: The proliferation of biomedical literature makes it increasingly difficult for researchers to find and manage relevant information. However, identifying research articles containing mutation data, a requisite first step in integrating large and complex mutation data sets, is currently tedious, time-consuming and imprecise. More effective mechanisms for identifying articles containing mutation information would be beneficial both for the curation of mutation databases and for individual researchers. We develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…‘McDonald et al. (17) explored an automated method for effective identification of appropriate research articles. This study developed an automated method using information extraction, classifiers and relevance ranking techniques to determine the likelihood of MEDLINE abstracts containing the relevant information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…‘McDonald et al. (17) explored an automated method for effective identification of appropriate research articles. This study developed an automated method using information extraction, classifiers and relevance ranking techniques to determine the likelihood of MEDLINE abstracts containing the relevant information.…”
Section: Resultsmentioning
confidence: 99%
“…This was achieved by training the algorithm on a subset of articles, based on identification of relevant keywords. The results of the study showed that the proposed automated system could effectively identify articles relevant to the immediate question and may prove to be a powerful tool for the broader research community (17). The principle difference between the previous automated searches (16, 17) lies in the intuitive learning nature of the algorithm proposed here, where in each iteration, an adaptive feedback step is employed to increase the search coverage.…”
Section: Resultsmentioning
confidence: 99%
“…In a first naive step, we checked the complete set of Medline abstracts (version as of April 26, 2007) to see if a regular expression finding mentions of [rR] [sS][ ]*[0-9][0-9]* in articles published after the year 2000 would be sufficient for the task. With this approach, we could guarantee a recall of 100% and checked the precision by subsampling of 300 mentions from the number of all mentions matching the regular expression (3,030). The ambiguity of rs number mentions was surprisingly high, which resulted in a precision of only 74%.…”
Section: Evaluation Of Direct Rs Number Extractionmentioning
confidence: 99%
“…3 This kind of information will allow semantic searches like, "Give me all articles mentioning a variation and diabetes." It is obvious that this will be of great help in the design of genetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts are being made for the extraction of interesting and complex patterns from non-structured text documents in the immunological domain. Examples include categorization of allergen cross-reactivity information [22], identification of cancer-associated gene variants [23], and the classification of immune epitopes [24].…”
Section: Computational Toolsmentioning
confidence: 99%